Descriptive study of the perception of the psychotherapeutic relationship in patients from the city of San Luis - García, Horacio Daniel (2019)
To investigate the patient’s perception of the therapeutic relationship and assessments about the therapist which could be facilitating, we designed a study using a non-probabilistic sample composed by 108 patients (M = 31.90, SD = 11.54), residents in San Luis, Argentina. The Helping Alliance Questionnaire - HAq-II was used (Luborsky et al., 1996) and a questionnaire built ad hoc, too. In general, the results show an appropriate therapeutic relationship and a high rating of therapist aspects such as warmth, seriousness, understanding, trust, respect, interest and commitment. Women therapists obtained higher scores in warmth and seriousness, trust, commitment to work, among others. Patients without knowledge of the different psychotherapy approaches tend to assess more positively relational aspects of the therapeutic relationship; meanwhile those who have knowledge have higher expectations about the results that are intended to be achieved.